STRATEGI PEMASARAN UNTUK MENINGKATKAN VOLUME PENJUALAN PADA UMKM EDI JAMUR DI KELURAHAN BAGAN PETE KOTA JAMBI - As’ad Isma; Khairiyani; Supiyah (CV. KAMPUS AKADEMIK PUBLISING, 2023)
Micro, small and medium enterprises are one of the most important parts of the Indonesian economy that are able to reduce poverty. The purpose of this study is to find out how the marketing strategy is applied to Edi Mushroom SMEs to increase sales volume and to find out what are the strengths, weaknesses, opportunities and threats to Edi Mushroom SMEs. The research method used is SWOT analysis. The results obtained in this study are the strategy implemented by UMKM Edi Mushrooms to increase sales volume covering 4P, namely in terms of products providing good quality and complete products, in terms of price providing relatively cheap prices, in terms of strategically selected locations and from in terms of promotion only through Whatsapp and word of mouth. The strengths of UMKM Edi Mushrooms are complete products, affordable prices, strategic locations and prioritizing product quality to maintain consumer loyalty. The weaknesses are the unstable weather, no special logo and less than optimal promotion. The opportunities are increasing population, increasing market needs and technological developments for promotion. The threat is competing with the same product and business locations that are next to competitors.